TiO2 doped polymer dispersed and stabilised liquid crystal smart film with high contrast ratio, low driving voltage and short response time. Issue 12 (26th September 2022) - Wang, Xiao; Hu, Wei; Chen, Gang; Chen, Hongren; Huang, Rui; Ren, Yunxiao; Xu, Jianjun; Hu, Junmei; Zhang, Lanying; Yu, Meina; Zhang, Haiquan; Yang, Huai
ABSTRACT: Due to the switchability between transparent and light-scattering states, polymer-dispersed liquid crystals (PDLCs) are widely used as smart windows, flexible display devices, projectors and other devices. In this work, we propose a new composite system containing TiO2 nanoparticles (NPs), liquid crystals and polymer that have low driving voltage, high contrast ratio (CR) and quick response ability. Distinguishing from the traditional PDLC system, the coexisting structure of vertically oriented polymer fibres (VOPFs) inside the porous polymer matrix was constructed and the TiO2 nanoparticle (NP) after functionalisation was introduced. It was found that the introduction of an appropriate amount of functionalised TiO2 NPs can effectively improve the electro-optical properties of the composite system. This new system provides a new idea for solving the compatibility problem of inorganic particles and organic matter. Graphical Abstract: uf0001